HANS JONAS'S " RESPONSIBILITY" ETHICS" PHILOSOPHICAL ANTHROPOLOGY IN CONTEXT - Vardo Beridze (Innovate Conferences, 2025)
The paper discusses the anthropological-ontological possibility of a philosophy of responsibility. This Approach The basis is Responsibility as Human Essence . Responsibility understood - Human Answer His/Her Freedom On the challenge , is your own existence Conscious Definition Necessity . It, As difficult as Structured Phenomenon Requires Systematic analysis .